Особенности развития видов рода Juglans L. при интродукции в Донецком ботаническом саду НАН Украины - Васильченко, А.А. (Промышленная ботаника, 2002)
Biological characteristics of the genus Juglans L. species under introduction in the Donetsk botanical garden, Nat. Acad. of Sci. of Ukraine are cited. On the basis of the dendrometry characteristics, as well as on the analysis of phenorhythmotypes, 3 species (Juglans regia L., Juglans nigra L., Juglans cinerea L.) are recommended for the use in the greenery planting as the most adjusted to the Donbass conditions.